(untitled) (International Seven Journal of Multidisciplinary, 2023)
Due to the problems that fossil origin energy brings, the global trend is to substitute this type of source for alternatives that generate a lower impact on the environment, among them, the use of biomass residues generated by the agro-industry, through the briquetting process. At the same time, the preservation of the Amazon has been violated, among other factors, for the production of firewood. Thus, the objective of this work is to conduct a preliminary study of a briquetting plant as a sustainable destination for the residues generated in the cupuaçu processing industry, whose production occurs on a large scale in the state of Amazonas. The research on the market and production was done through Google, the plant design, costs and economic analysis were based on the Manual Plant Design and Economics for Engineers. The Brazilian briquette market presents great potential. For the project a total of 5,000 t/year of wet raw material produced was considered. The total initial investment capital resulted in the value of R 1.590.525,56. The suggested price to be practiced is R455.00/ton and, considering the production of 3,217.77 tons per year, the annual revenue is R1,488,655.35. The annual gross profit resulted in R 677,257.64 and the net profit resulted in R 654,966.96 per year, disregarding depreciation. The working capital resulted in R587,943.96 per year. The number of years to pay off the investment was 2.7 years. The preliminary analysis of the project shows economic viability, however for the technical analysis more tests are needed. DOI:https://doi.org/10.56238/isevmjv2n2-003